We are searching data for your request:

**Forums and discussions:**

**Manuals and reference books:**

**Data from registers:**

**Wait the end of the search in all databases.**

Upon completion, a link will appear to access the found materials.

Upon completion, a link will appear to access the found materials.

Let's check:

Let a and b be real, where a and b are nonzero. Suppose a = b.

So if a = b, multiplying both sides of equality by *The* we have:

The^{2}= ab

Subtracting *B ^{2}* on both sides of equality we have:

The^{2}-B^{2}= ab-b^{2}

We know (factorization) that *The ^{2}-B^{2}= (a + b) (a-b)*. Soon:

(a + b) (a-b) = ab-b^{2}

Putting *B* in evidence on the right side we have:

(a + b) (a-b) = b (a-b)

Dividing both sides by *(a-b)* we have:

a + b = b

As at the beginning we said that *a = b*so instead of *The* I can put *B*:

b + b = b

Therefore *2b = b*. Dividing both sides by *B* we finally came to the conclusion:

**2=1**

Obviously this demonstration has an error because we all know that 2 is not equal to 1 (or does anyone have any questions?). Click below to find out what the error is:

In this demonstration comes a stage where we have:**(a + b) (a-b) = b (a-b)**

According to the demonstration, the next step would be:

**We divided** both sides by **(a-b)**.

**There is the mistake !!!**

At first we assume a = b, so we have to **a-b = 0**.

**Division by zero does not exist !!!**